Proceedings of the 18th ACM Conference on Innovation and Technology in Computer Science Education 2013
DOI: 10.1145/2462476.2466519
|View full text |Cite
|
Sign up to set email alerts
|

Making computing interesting to school students

Abstract: It is widely agreed that there is a need to excite more school students about computing. Considering teachers' views about student engagement is important to securing their support for any solution. We therefore present the results of a qualitative, questionnaire-based study on teachers' perceptions of the best ways to make the subject interesting. From 115 responses by UK computing teachers emerged a range of themes about the issues they felt were most important. We found that whilst their views reflected a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 18 publications
0
21
0
1
Order By: Relevance
“…The school curriculum is a complex environment where multiple competing priorities exist (Settle et al, 2012), and thus it is difficult for the in-service teachers to change and add one big concept into the already busy curriculum without support from management. Academics and industry could do more to engage with teachers, especially if they wish to introduce deep computational thinking principles in schools (Black et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The school curriculum is a complex environment where multiple competing priorities exist (Settle et al, 2012), and thus it is difficult for the in-service teachers to change and add one big concept into the already busy curriculum without support from management. Academics and industry could do more to engage with teachers, especially if they wish to introduce deep computational thinking principles in schools (Black et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Providing teachers with adequate teaching-related resources is critical in order to improve student outcomes (Stevens et al, 2013). Black et al (2013) suggest that creating communities of practice could allow teachers to share the resources and provide each other with ongoing support.…”
Section: Teaching Computational Thinking and The Challenges Involvedmentioning
confidence: 99%
“…Black et al carried out a study in the UK where they asked Computing teachers how they felt they could make the subject interesting (Black et al 2013). The key aspects that they identified were the importance to teachers of making Computing fun and relevant.…”
Section: The Teachers' Perspectivementioning
confidence: 99%
“…There is an additional role for those in higher education (Computer Science and Education) departments to support the teachers with subject knowledge. Universities are a great resource for teachers seeking to increase their subject knowledge [Black et al 2013] and those in the UK have shown a great willingness to support teachers in this way.…”
Section: Localmentioning
confidence: 99%